The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5539/jas.v6n2p24
|View full text |Cite
|
Sign up to set email alerts
|

Biochar Can Enhance Potassium Fertilization Efficiency and Economic Feasibility of Maize Cultivation

Abstract: Field experiments were conducted to study the effect of biochar on potassium fertilizer leaching and uptake, efficiency and effectiveness of K fertilization, and economic viability of farming maize. Thirty tons ha -1 of biochar prepared from organic waste was applied to an Inceptisol. The experiment was arranged in a randomized block design with 7 treatments, namely control (without biochar and KCl), K1 (200 kg ha -1 KCl), BK0 (biochar, without KCl), BK1/4 (biochar + 50 kg ha -1 KCl), BK 1/2 (biochar + 100 kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 12 publications
2
17
0
1
Order By: Relevance
“…Increase in soil K by up to 189% with biochar treatment was reported by Widowati et al (2012) and in a study by Widowati and Asnah (2014), soil available K was observed to be higher (69-89%) as a result of biochar treatment. Soil K was observed to be higher by up to 14% with biochar treatment in an experiment conducted by Nigussie et al (2012).…”
Section: Resultsmentioning
confidence: 68%
“…Increase in soil K by up to 189% with biochar treatment was reported by Widowati et al (2012) and in a study by Widowati and Asnah (2014), soil available K was observed to be higher (69-89%) as a result of biochar treatment. Soil K was observed to be higher by up to 14% with biochar treatment in an experiment conducted by Nigussie et al (2012).…”
Section: Resultsmentioning
confidence: 68%
“…The increase in the phosphorus content in the soil after the application of biochar results from the content of easily absorbable forms of this element in biochars, as well as from its ability to react on the soil reaction, thus producing changes in the solubility of phosphorus forms [31,32]. Numerous authors report that the addition of biochars to the soil affects the intensive growth of soluble forms of potassium in the soil solution [33,34]. Liu et al [35] note an increase in the contents of macroelements in the soil compared to the control following the application of biochar from the vegetative parts of bamboo and rice straw.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 Biochar had some good characteristics, including being rich in nutrients, improving the nutrient utilization efficiency of crops, adjusting soil pH and removal of soil pollutants, etc. [48][49][50][51][52] Due to these characteristics, biochar could improve the soil quality, thus the research concerning biochar and soil(s) were relatively hotter. The further analysis of these 2062 articles containing soil or soils revealed that "carbon" and "effects" were the rst and second most used words, aer soil(s) and biochar.…”
Section: Title Analysismentioning
confidence: 99%